Monodisperse copper sulfide quantum dot and preparation method and application of nano composite material of monodisperse copper sulfide quantum dot
By using copper-organic sulfur complex as the precursor, monodispersed copper sulfide quantum dots are generated by heating reactions, and the problems of poor dispersion and low catalytic activity of copper sulfide quantum dots in the prior art are solved, and efficient catalytic activity and convenient recycling and reuse are achieved.
Patent Information
- Application Number
- CN202510048305.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The prior art is difficult to effectively prepare monodispersed, uniform sized ultra-small particle size (less than 10 nm) copper sulfide quantum dots, and their dispersion and low catalytic activity are poor, making it difficult to apply to the field of peroxidase-like catalysis.
The copper-organic sulfur complex is used as the precursor to generate monodispersed copper sulfide quantum dots through heating reactions, and the particle size and loading are controlled by adjusting the reaction temperature and the ratio of the copper complex to form nanocomposites to improve dispersion and catalytic activity.
The preparation of monodispersed, uniform size copper sulfide quantum dots is achieved, which improves its activity in peroxidase-like catalysts, and the design of nanocomposite materials is conducive to the recovery and reuse of catalysts.
Smart Images

Figure CN119873874A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a preparation method and application of monodisperse copper sulfide quantum dots and nanocomposite materials thereof. Background Art
[0002] Nano copper sulfide has good chemical stability, low toxicity, good biocompatibility and photothermal properties, and has application prospects in antibacterial and tumor treatment. At present, researchers have prepared copper sulfide nanomaterials with different morphologies such as nanoparticles, nanosheets, and nanorods through various synthesis methods such as solvent thermal, precipitation, thermal decomposition, and template methods, but there are still few reports on copper sulfide quantum dots with ultra-small particle sizes (less than 10nm).
[0003] The synthesis of copper sulfide quantum dots is mainly based on the liquid phase method, usually using copper salts, surfactants and sodium sulfide as raw materials to generate ultra-small copper sulfide nanoparticles in the aqueous phase. For example, in the article "Biodegradable Quantum Composites for Synergistic Photothermal Therapy and Copper-Enhanced Chemotherapy", polyvinyl pyrrolidone was used as a surfactant, and sodium sulfide solution was added to the copper chloride solution to generate water-dispersible copper sulfide quantum dots, but the size distribution of the CuS quantum dots prepared by this method was wide and the performance was poor.
[0004] Moreover, when preparing copper sulfide nanoclusters, due to the small particle size and high surface energy of copper sulfide nanoclusters, they are very easy to agglomerate to form larger nanoparticles, and have poor dispersion, which will result in a decrease in specific surface area and a reduction in effective active sites, especially after drying, making it difficult to redisperse, thereby reducing its enzyme-like catalytic activity; and highly dispersed ultra-small copper sulfide nanoparticles have the problem of difficulty in separation and recovery, which still needs further research and improvement. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing and using monodisperse copper sulfide quantum dots and nanocomposites thereof, so as to solve the above-mentioned problems in the background technology. The present invention uses a copper-organic sulfur complex as a precursor and obtains monodisperse copper sulfide quantum dots of uniform size by a simple heating method. In addition, the present invention can adjust the particle size of copper sulfide nanoparticles by adjusting the reaction temperature, and the loading amount of copper sulfide can be adjusted by adjusting the ratio of the copper complex and the carrier. The prepared copper sulfide nanocomposite has good peroxidase-like catalytic activity.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a monodisperse copper sulfide quantum dot catalyst, comprising the following steps:
[0008] Mixing a copper salt and a sulfur source in water to form a precursor solution;
[0009] Continuously adding ammonia water to the precursor solution until the reaction system is turbid first and then clear, reacting, and collecting solid phase components to obtain a copper sulfide quantum dot precursor;
[0010] The copper sulfide quantum dot precursor is mixed with an organic solvent to obtain a mixed solution, which is heated for reaction to obtain the monodispersed copper sulfide quantum dot catalyst.
[0011] In the process of adding ammonia water, it is necessary to continue adding ammonia water until the reaction system is first turbid and then completely clear to avoid the incorporation of copper hydroxide impurities into the copper sulfide quantum dot precursor.
[0012] Preferably, the sulfur source is thiamine and / or thiamine salts (vitamin B1); the thiamine salts include one or more of thiamine hydrochloride, thiamine nitrate and thiamine sulfate; the copper salt includes one or more of copper nitrate, copper sulfate, copper chloride and copper acetate.
[0013] Preferably, the molar ratio of the copper salt to the sulfur source is 1:1 to 1:4, more preferably 3:4 to 1:2.
[0014] Preferably, the reaction time is 1 to 4 hours.
[0015] In the preparation scheme of the present invention, when the amount of copper salt added is too little, the amount of copper sulfide quantum dot precursor generated is too low; when the amount of copper salt added is too much, it will cause waste of copper salt, and the optimal ratio is 3:4 to 1:2.
[0016] Preferably, the heating reaction temperature is 100 to 180° C., more preferably 120 to 140° C., further preferably 140° C., and the time is 1 to 6 hours, more preferably 2 to 4 hours; and / or
[0017] The concentration of the copper sulfide quantum dot precursor in the mixed solution is 10 to 100 mg / mL, more preferably 40 to 60 mg / mL; and / or
[0018] The organic solvent is dimethyl sulfoxide or N,N-dimethylformamide.
[0019] When the concentration of the copper sulfide quantum dot precursor is too low, the amount of copper sulfide quantum dots generated is small; when the concentration is too high, the particle size of the copper sulfide quantum dots generated will increase excessively.
[0020] The reaction temperature of the present invention cannot be too low, otherwise it will lead to a slower generation rate of copper sulfide quantum dots and require a longer reaction time.
[0021] More preferably, the process of preparing the mixed solution further comprises the step of adding a carrier material; the method of adding the carrier material is: mixing the copper sulfide quantum dot precursor, the carrier material and an organic solvent to obtain a mixed solution.
[0022] More preferably, the carrier material is carbon nitride, silicon dioxide, a carbon material or a metal oxide; and the mass ratio of the copper sulfide quantum dot precursor to the carrier material is 3:1 to 1:5.
[0023] More preferably, the metal oxide is titanium dioxide, aluminum oxide or cerium oxide.
[0024] The second technical solution of the present invention is to provide a monodisperse copper sulfide quantum dot catalyst obtained according to the above preparation method.
[0025] The third technical solution of the present invention is to provide an application of the above-mentioned monodisperse copper sulfide quantum dot catalyst in the field of peroxidase-like catalysts.
[0026] Under normal circumstances, the copper ions in copper salts cannot react with thiamine and its salts (vitamin B1) to form copper complexes, and vitamin B1 is not a sulfur source in the usual sense. However, under the reaction conditions of the present invention, since the added ammonia water can adjust the solution to alkaline (pH value ≥ 9), thiamine and its salts are decomposed, the carbon-sulfur bond of the thiazole ring is broken, and a carbonyl group and a sulfur anion are generated. Then, the carbonyl group reacts with the amino group on the benzene ring through a Schiff base to form a naphthalene heterocycle. Subsequently, the sulfur anion can coordinate with the copper ion under heating conditions to form CuS nanoclusters (see Fig.14 ).
[0027] The beneficial technical effects of the present invention are as follows:
[0028] The present invention uses a copper-organic sulfur complex as a precursor and obtains monodisperse copper sulfide quantum dots with uniform size by a simple heating method. In addition, the present invention can adjust the particle size of copper sulfide nanoparticles by adjusting the reaction temperature, and the loading amount of copper sulfide can be adjusted by adjusting the ratio of the copper complex and the carrier. The prepared copper sulfide nanocomposite material has good peroxidase-like catalytic activity.
[0029] The present invention loads copper sulfide nanoclusters onto a carrier material to form a nanocomposite material, which can effectively prevent the agglomeration of copper sulfide nanoclusters and is conducive to the recovery and reuse of the catalyst. When the catalyst is prepared into a product form of a nanocomposite material, the particle size of the copper sulfide nanoparticles in the copper sulfide nanocomposite material is 3 to 8 nm.
[0030] The preparation method of the invention is simple and convenient; the prepared copper sulfide nanocomposite material can effectively prevent the agglomeration of ultra-small copper sulfide nanoparticles and has good application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is the energy spectrum of the copper sulfide quantum dot precursor prepared in Example 1.
[0033] Figure 2 TEM images of copper sulfide quantum dots prepared in Example 1 at different magnifications.
[0034] Figure 3 This is an XPS graph of copper sulfide quantum dots prepared in Example 1. Wherein, (a) is the 2p orbital of the copper element, and (b) is the 2p orbital of the sulfur element.
[0035] Figure 4 TEM images of copper sulfide quantum dots prepared in Example 2 at different magnifications.
[0036] Figure 5 TEM images of copper sulfide quantum dots prepared in Example 3 at different magnifications.
[0037] Figure 6 TEM images of the copper sulfide nanocomposite prepared in Example 4 at different magnifications.
[0038] Figure 7 This is an XPS graph of the copper sulfide nanocomposite prepared in Example 4. Wherein, (a) is the 2p orbital of the copper element, and (b) is the 2p orbital of the sulfur element.
[0039] Figure 8 This is a characterization diagram of the peroxidase-like properties of the copper sulfide nanocomposite prepared in Example 4.
[0040] Fig. 9 TEM images of the copper sulfide nanocomposite prepared in Example 5 at different magnifications.
[0041] Fig.10 TEM images of the copper sulfide nanocomposite prepared in Example 6 at different magnifications.
[0042] Fig.11TEM images of the copper sulfide nanocomposite prepared in Example 7 at different magnifications.
[0043] Fig.12 TEM images of the copper sulfide nanocomposite prepared in Example 8 at different magnifications.
[0044] Fig.13 This is a characterization diagram of the peroxidase-like properties of the copper sulfide nanocomposite prepared in Example 8.
[0045] Fig.14 This is the reaction formula for preparing copper sulfide quantum dots in the present invention.
[0046] Fig.15 TEM images of the copper sulfide nanocomposite prepared in Example 9 at different magnifications.
[0047] Fig.16 TEM images of the copper sulfide nanocomposite prepared in Example 10 at different magnifications.
[0048] Fig.17 TEM images of the copper sulfide nanocomposite prepared in Example 11 at different magnifications. DETAILED DESCRIPTION
[0049] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0050] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0052] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0053] Fig.14This is the reaction formula for preparing copper sulfide quantum dots in the present invention (taking vitamin B1 as an example as the sulfur source).
[0054] The "room temperature" in the present invention is 10-30°C unless otherwise specified.
[0055] The concentration of ammonia water used in the following examples of the present invention is between 25 and 28 wt %.
[0056] All raw materials used in the following embodiments of the present invention are commercially available products.
[0057] Example 1
[0058] A method for preparing monodisperse copper sulfide quantum dots, the steps are as follows:
[0059] Weigh 6.7 g of thiamine hydrochloride and 1.7 g of cupric chloride dihydrate respectively and dissolve them in 200 mL of pure water, stir evenly to form a precursor solution; add ammonia water dropwise to generate a light blue precipitate, and then continue to add ammonia water dropwise until the precipitate is completely dissolved to form a blue copper ammonia solution (in the process of adding ammonia water, Cu(OH)2 precipitate is first generated, and then continue to add ammonia water to dissolve the precipitate to form a copper ammonia solution, which is alkaline); then stir for 2 hours to allow the reaction system to fully form a yellow copper complex precipitate, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0060] Weigh 2.0 g of copper sulfide quantum dot precursor and add it to 50 mL of dimethyl sulfoxide. After stirring to dissolve, heat the mixture in an oil bath at 140°C for 4 h, then cool it naturally to room temperature, centrifuge it, wash it with pure water, and ultrasonically disperse it in water to obtain a dispersion of monodispersed copper sulfide quantum dots.
[0061] The copper sulfide quantum dot precursor synthesized in Example 1 was characterized by an energy spectrum. The method is as follows: the copper sulfide quantum dot precursor was spread on a single crystal silicon wafer, and after platinum plating using an ion sputtering instrument, an energy spectrum was characterized on a field emission scanning electron microscope. The results are as follows: Figure 1 shown.
[0062] Figure 1 This is the energy spectrum of the copper sulfide quantum dot precursor prepared in Example 1.
[0063] Depend on Figure 1 It can be seen that it contains both copper and sulfur elements.
[0064] The copper sulfide quantum dots prepared in Example 1 were characterized by transmission electron microscopy. Figure 2 shown.
[0065] Figure 2 TEM images of copper sulfide quantum dots prepared in Example 1 at different magnifications.
[0066] Depend on Figure 2 It can be seen that the copper sulfide quantum dots prepared in Example 1 have good monodispersity and narrow particle size distribution, with an average particle size of about 3.5 nm.
[0067] The copper sulfide quantum dots prepared in Example 1 were characterized by X-ray photoelectron spectroscopy (XPS). Figure 3 shown.
[0068] Figure 3 This is an XPS graph of copper sulfide quantum dots prepared in Example 1. Wherein, (a) is the 2p orbital of the copper element, and (b) is the 2p orbital of the sulfur element.
[0069] Depend on Figure 3 It can be seen that the copper element binding energy peaks at 932.4eV and 953.2eV correspond to divalent copper 2p 3 / 2 and 2p 1 / 2 The electron binding energy of sulfur appears at 161.5eV and 162.7eV. 2- 2p 3 / 2 and 2p 1 / 2 The electron binding energy peak of 1.34 W / cm3 proves that the prepared ultrasmall nanoparticles are copper sulfide quantum dots.
[0070] Example 2
[0071] A method for preparing monodisperse copper sulfide quantum dots, the steps are as follows:
[0072] Weigh 3.6 g of thiamine nitrate and 0.6 g of copper nitrate trihydrate respectively and dissolve them in 200 mL of pure water, stir evenly to form a precursor solution; add ammonia water to generate a light blue precipitate, and then continue to add ammonia water until the precipitate is completely dissolved to form a blue copper ammonia solution; then stir for 4 hours, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0073] Weigh 0.5 g of copper sulfide quantum dot precursor and add it to 50 mL of dimethyl sulfoxide. After stirring to dissolve, heat it in an oil bath at 160°C for 2 h, then cool it naturally to room temperature, centrifuge it, wash it with pure water, and ultrasonically disperse it in water to obtain a dispersion of monodisperse copper sulfide quantum dots.
[0074] Figure 4 TEM images of copper sulfide quantum dots prepared in Example 2 at different magnifications.
[0075] like Figure 4 As shown, copper sulfide quantum dots have good monodispersity, particle size distribution is mainly between 4 and 8 nm, and the average particle size is about 6.6 nm.
[0076] Example 3
[0077] A method for preparing monodisperse copper sulfide quantum dots, the steps are as follows:
[0078] Weigh 10 g of thiamine hydrochloride and 5 g of copper sulfate pentahydrate respectively, dissolve them in 250 mL of pure water, stir evenly to form a precursor solution; add ammonia water to generate a light blue precipitate, and then continue to add ammonia water until the precipitate is completely dissolved to form a blue copper ammonia solution; then stir for 3 hours, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0079] Weigh 1 g of copper sulfide quantum dot precursor and add it to 20 mL of N,N-dimethylformamide. After stirring to dissolve, heat the reaction in a 100°C oil bath for 6 h, then naturally cool to room temperature, centrifuge, wash with pure water, and ultrasonically disperse in water to obtain a dispersion of monodisperse copper sulfide quantum dots.
[0080] Figure 5 TEM images of copper sulfide quantum dots prepared in Example 3 at different magnifications.
[0081] like Figure 5 As shown, copper sulfide quantum dots have good monodispersity and an average particle size of about 2.6 nm.
[0082] Example 4
[0083] A method for preparing a copper sulfide nanocomposite material, comprising the following steps:
[0084] Weigh 3.4 g of thiamine hydrochloride and 1.25 g of copper sulfate pentahydrate respectively and dissolve them in 50 mL of pure water, stir evenly to form a precursor solution; add ammonia water to generate a light blue precipitate, and then continue to add ammonia water until the precipitate is completely dissolved to form a blue copper ammonia solution; then stir for 2 hours, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0085] Weigh 0.5g of copper sulfide quantum dot precursor and add it to 10mL of dimethyl sulfoxide to obtain a copper complex solution; weigh 2.5g of graphite phase carbon nitride (g-C3N4) and ultrasonically disperse it in 75mL of dimethyl sulfoxide to form a dispersion. Under stirring, add the copper complex solution to the dispersion, stir for 30min, heat in an oil bath at 180℃ for 1h, then naturally cool to room temperature, centrifuge, and wash with pure water to obtain a graphite phase carbon nitride supported copper sulfide nanocomposite (CuS@g-C3N4).
[0086] Figure 6 TEM images of the copper sulfide nanocomposite prepared in Example 4 at different magnifications.
[0087] like Figure 6 As shown, ultra-small copper sulfide nanoparticles are evenly distributed on the surface of g-C3N4, and the average particle size of the copper sulfide nanoparticles is about 8nm.
[0088] Figure 7 This is an XPS graph of the copper sulfide nanocomposite prepared in Example 4. Wherein, (a) is the 2p orbital of the copper element, and (b) is the 2p orbital of the sulfur element.
[0089] Figure 7 Among them, copper element is mainly +2 valence, and sulfur element is -2 valence; the atomic fractions of copper and sulfur are 6.26% and 7.16% respectively.
[0090] Effect Example 1
[0091] Weigh 10 mg of the CuS@g-C3N4 prepared in Example 4 and ultrasonically disperse it in 5 mL of water to prepare a CuS@g-C3N4 dispersion. Take 0.5 mL of acetic acid-sodium acetate buffer solution (0.2 mol / L, pH = 4) in a test tube, then add 10 μL of 3,3',5,5'-tetramethylbenzidine (50 mmol / L), 10 μL of hydrogen peroxide solution (250 mmol / L) and 10 μL of CuS@g-C3N4 dispersion, shake well and react for 10 minutes, the solution turns dark blue ( Figure 8 The left three test tubes are marked as TMB+CuS@g-C3N4+H2O2). Figure 8 The left test tube is TMB+H2O2) and the one without hydrogen peroxide ( Figure 8 The second test tube from the left, denoted as TMB+CuS@g-C3N4) was used as a control group. The control experiment showed no obvious phenomenon, indicating that the CuS@g-C3N4 nanocomposite material prepared in Example 4 has peroxidase-like activity.
[0092] Figure 8 This is a characterization diagram of the peroxidase-like properties of the copper sulfide nanocomposite prepared in Example 4.
[0093] Figure 8 In the figure, the first test tube from the left, the second test tube from the left, and the third test tube from the left are TMB+H2O2, TMB+CuS@g-C3N4, and TMB+CuS@g-C3N4+H2O2, respectively.
[0094] Example 5
[0095] A method for preparing a copper sulfide nanocomposite material, comprising the following steps:
[0096] Weigh 3.4 g of thiamine hydrochloride and 1.25 g of copper sulfate pentahydrate respectively and dissolve them in 50 mL of pure water, stir evenly to form a precursor solution; add ammonia water to generate a light blue precipitate, and then continue to add ammonia water until the precipitate is completely dissolved to form a blue copper ammonia solution; then stir for 2 hours, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0097] Weigh 0.5g of copper sulfide quantum dot precursor and add it to 10mL of dimethyl sulfoxide to obtain a copper complex solution; weigh 0.75g of cerium dioxide (CeO2) and ultrasonically disperse it in 75mL of dimethyl sulfoxide to form a dispersion. Under stirring, add the copper complex solution to the dispersion, stir for 30 minutes, heat in an oil bath at 140℃ for 4 hours, then naturally cool to room temperature, centrifuge, and wash with pure water to obtain a cerium dioxide-loaded copper sulfide nanocomposite (CuS@CeO2).
[0098] Fig. 9 TEM images of the copper sulfide nanocomposite prepared in Example 5 at different magnifications.
[0099] like Fig. 9 As shown, it can be clearly seen that ultra-small copper sulfide nanoparticles are coated on the surface of CeO2, and the average particle size of the copper sulfide nanoparticles is about 3-5nm.
[0100] Example 6
[0101] A method for preparing a copper sulfide nanocomposite material, comprising the following steps:
[0102] Weigh 6.8 g of thiamine hydrochloride and 1.7 g of hydrated copper chloride respectively and dissolve them in 50 mL of pure water, stir evenly to form a precursor solution; add ammonia water to generate a light blue precipitate, and then continue to add ammonia water until the precipitate is completely dissolved to form a blue copper ammonia solution; then stir for 4 hours, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0103] 1.0g of copper sulfide quantum dot precursor was weighed and added to 20mL of N,N-dimethylformamide (DMF) to obtain a copper complex solution; 1.0g of nano carbon black (XC-72) was weighed and ultrasonically dispersed in 50mL of DMF to form a dispersion. Under stirring, the copper complex solution was added to the dispersion, stirred for 1h, heated in an oil bath at 140℃ for 4h, then naturally cooled to room temperature, centrifuged, and washed with pure water to obtain a carbon black-loaded copper sulfide nanocomposite (CuS@XC-72).
[0104] Fig.10 TEM images of the copper sulfide nanocomposite prepared in Example 6 at different magnifications.
[0105] like Fig.10 As shown, ultra-small copper sulfide nanoparticles are evenly distributed on the surface of XC-72, and the average particle size of the copper sulfide nanoparticles is about 4 nm.
[0106] Example 7
[0107] A method for preparing a copper sulfide nanocomposite material, comprising the following steps:
[0108] Weigh 6.8 g of thiamine hydrochloride and 1.7 g of hydrated copper chloride respectively and dissolve them in 50 mL of pure water, stir evenly to form a precursor solution; add ammonia water to generate a light blue precipitate, and then continue to add ammonia water until the precipitate is completely dissolved to form a blue copper ammonia solution; then stir for 4 hours, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0109] 1.0g of copper sulfide quantum dot precursor was weighed and added to 20mL of dimethyl sulfoxide to obtain a copper complex solution; 2.0g of nano-alumina (Al2O3) was weighed and ultrasonically dispersed in 100mL of dimethyl sulfoxide to form a dispersion. Under stirring, the copper complex solution was added to the dispersion, stirred for 30min, heated in an oil bath at 160℃ for 3h, then naturally cooled to room temperature, centrifuged, and washed with pure water to obtain a cerium dioxide-loaded copper sulfide nanocomposite material (CuS@Al2O3).
[0110] Fig.11 TEM images of the copper sulfide nanocomposite prepared in Example 7 at different magnifications.
[0111] like Fig.11 As shown, ultra-small copper sulfide nanoparticles are evenly distributed on the Al2O3 surface, and the average particle size of the copper sulfide nanoparticles is about 8nm.
[0112] Example 8
[0113] A method for preparing a copper sulfide nanocomposite material, comprising the following steps:
[0114] Weigh 6.8 g of thiamine hydrochloride and 1.7 g of hydrated copper chloride respectively and dissolve them in 50 mL of pure water, stir evenly to form a precursor solution; add ammonia water to generate a light blue precipitate, and then continue to add ammonia water until the precipitate is completely dissolved to form a blue copper ammonia solution; then stir for 4 hours, filter, wash with pure water, and vacuum dry to obtain a yellow powdery copper sulfide quantum dot precursor.
[0115] 0.3g of copper sulfide quantum dot precursor was weighed and added to 10mL of dimethyl sulfoxide to obtain a copper complex solution; 0.1g of graphene oxide (GO) was weighed and ultrasonically dispersed in 20mL of dimethyl sulfoxide to form a dispersion. Under stirring, the copper complex solution was added to the dispersion, stirred for 30min, heated in an oil bath at 140℃ for 4h, then naturally cooled to room temperature, centrifuged, and washed with pure water to obtain graphene oxide-supported copper sulfide nanocomposite (CuS@GO).
[0116] Fig.12 TEM images of the copper sulfide nanocomposite prepared in Example 8 at different magnifications.
[0117] Effect Example 2
[0118] 10 mg of CuS@GO prepared in Example 8 was weighed and ultrasonically dispersed in 10 mL of water to prepare a CuS@GO dispersion. 0.5 mL of acetic acid-sodium acetate buffer solution (0.2 mol / L, pH = 4) was taken into a test tube, and then 10 μL of 3,3',5,5'-tetramethylbenzidine (50 mmol / L), 10 μL of hydrogen peroxide solution (250 mmol / L) and 10 μL of CuS@GO dispersion were added. After shaking and reacting for 10 minutes, the solution turned dark blue ( Fig.13 The left three test tubes are marked as TMB+CuS@GO+H2O2). Fig.13 The left test tube is TMB+H2O2) and the one without hydrogen peroxide ( Fig.13 The test group of the second test tube from the left, denoted as TMB+CuS@GO) was used as a control, and the control experiment showed no obvious phenomenon, indicating that the CuS@GO nanocomposite material prepared in Example 8 has peroxidase-like activity.
[0119] Fig.13 This is a characterization diagram of the peroxidase-like properties of the copper sulfide nanocomposite prepared in Example 8.
[0120] Fig.13 In the figure, the first test tube on the left, the second test tube on the left, and the third test tube on the left are TMB+H2O2, TMB+CuS@GO, and TMB+CuS@GO+H2O2, respectively.
[0121] Example 9
[0122] The only difference from Example 6 is that the temperature of the oil bath heating is changed to 160°C.
[0123] Example 10
[0124] The only difference from Example 9 is that the added amount of the copper sulfide quantum dot precursor is changed to 1.5 g.
[0125] Embodiment 11
[0126] The only difference from Example 9 is that the added amount of the copper sulfide quantum dot precursor is changed to 2.0 g.
[0127] Fig.15 TEM images of the copper sulfide nanocomposite prepared in Example 9 at different magnifications.
[0128] Fig.16 TEM images of the copper sulfide nanocomposite prepared in Example 10 at different magnifications.
[0129] Fig.17TEM images of the copper sulfide nanocomposite prepared in Example 11 at different magnifications.
[0130] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a monodisperse copper sulfide quantum dot catalyst, characterized in that: The following steps are involved: Mixing a copper salt and a sulfur source in water to form a precursor solution; Continuously adding ammonia water to the precursor solution until the reaction system is turbid first and then clear, reacting, and collecting solid phase components to obtain a copper sulfide quantum dot precursor; The copper sulfide quantum dot precursor is mixed with an organic solvent to obtain a mixed solution, which is heated for reaction to obtain the monodispersed copper sulfide quantum dot catalyst.
2. The preparation method according to claim 1, characterized in that: The sulfur source is thiamine and / or thiamine salts; the thiamine salts include one or more of thiamine hydrochloride, thiamine nitrate and thiamine sulfate; the copper salt includes one or more of copper nitrate, copper sulfate, copper chloride and copper acetate.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the copper salt to the sulfur source is 1:1 to 1:
4.
4. The preparation method according to claim 1, characterized in that: The reaction time is 1 to 4 hours.
5. The preparation method according to claim 1, characterized in that: The heating reaction temperature is 100-180°C and the time is 1-6h; and / or The concentration of the copper sulfide quantum dot precursor in the mixed solution is 10-100 mg / mL; and / or The organic solvent is dimethyl sulfoxide or N,N-dimethylformamide.
6. The preparation method according to claim 5, characterized in that: The process of preparing the mixed solution also includes the step of adding a carrier material; the method of adding the carrier material is: mixing the copper sulfide quantum dot precursor, the carrier material and an organic solvent to obtain a mixed solution.
7. The preparation method according to claim 6, characterized in that: The carrier material is carbon nitride, silicon dioxide, carbon material or metal oxide; the mass ratio of the copper sulfide quantum dot precursor to the carrier material is 3:1 to 1:
5.
8. A monodispersed copper sulfide quantum dot catalyst obtained according to the preparation method according to any one of claims 1 to 7.
9. Use of the monodisperse copper sulfide quantum dot catalyst according to claim 8 in the field of peroxidase-like catalysts.
Citation Information
Patent Citations
Preparation method of dendritic copper sulphide microcrystal
CN103232057A
Green simple synthesis method for cadmium sulfide quantum dot
CN107540012A
Copper sulfide nano material with peroxidase-like characteristics, preparation method and application thereof
CN112374527A